The removal of heavy metals from wastewater using South African clinoptilolite - Kapanji, Kutemba Kaina (My University, 2010)
This research concerns the further characterisation and establishment of adsorption behaviour of the South African clinoptilolite. Synthetic single- and multi-component wastewaters were used, and experiments conducted in both batch and column systems at 25oC ± 2. Wastewaters containing heavy metals ions Cu2+, Co2+, Ni2+ and Cr3+, were used at different feed concentrations (50 - 500 mg/L), and adsorbed onto natural and homoionic (Na+, K+, Ca2+, NH+ 4) forms of the zeolite. The Na+-form clinoptilolite had an improved cation exchange capacity over the natural one, and the selectivity series of metal ions by these two forms varied. Brunauer Emmett Teller surface area analysis carried out also confirms that preconditioning clinoptilolite with Na+ ions results in an increase in pore diameter, allowing for easier diffusion of ions and more adsorption. An atomic adsorption spectrophotometer (AAS) was used to analyse metal ions in solution. Adsorption efficiencies with over 75% of metal ions adsorbed in the first hour of contact were recorded, and complete adsorption equilibrium being reached in 4 hrs. Regeneration of Na+-form and natural clinoptilolite (using 0.5M NaCl stripping solution) initially showed an increase in loading capacities, then a decrease with the subsequent cycles. A comparison between two particle sizes revealed that smaller particle sized clinoptilolite have slightly higher adsorption capacities. The equilibrium data also fitted well with the linear form of the Langmuir and Freundlich isotherms at lower concentrations of 50 mg/L.
Thesis MSc Faculty of Engineering and the Built Environment,School of Chemical and Metallurgical Engineering, University of the Witwatersrand
Keywords: clinoptilolite; zeolites; water